The role of cavities in protein dynamics: Crystal structure of a photolytic intermediate of a mutant myoglobin - BRUNORI, Maurizio; VALLONE, Beatrice; CUTRUZZOLA', Francesca; TRAVAGLINI ALLOCATELLI, Carlo; J. Berendzen; K. Chu; R. M. Sweet; I. Schlichting (Proceedings of the National Academy of Sciences, 2000)
We determined the structure of the photolytic intermediate of a sperm whale myoglobin (Mb) mutant called Mb-YQR [Leu(B10)-->Tyr; His(E7)-->Gln; Thr(E10)-->Arg] to 1.4-Angstrom resolution by ultra-low temperature (20 K) x-ray diffraction. Starting with the CO complex, illumination leads to photolysis of the Fe-CO bond, and migration of the photolyzed carbon monoxide (CO*) to a niche in the protein 8.1 Angstrom from the heme iron; this cavity corresponds to that hosting an atom of Xe when the crystal is equilibrated with xenon gas at 7 atmospheres [Tilton, R. F,, Jr., Kuntz, I. D. & Petsko, G. A, (1984) Biochemistry 23, 2849-2857]. The site occupied by CO* corresponds to that predicted by molecular dynamics simulations previously carried out to account for the NO geminate rebinding of Mb-YQR observed in laser photolysis experiments at room temperature. This secondary docking site differs from the primary docking site identified by previous crystallographic studies on the photolyzed intermediate of wild-type sperm whale Mb performed at cryogenic temperatures [Teng et al. (1994) Nat Struct. Biol, 1, 701-705] and room temperature [Srajer et al, (1996) Science 274, 1726-1729]. Our experiment shows that the pathway of a small molecule in its trajectory through a protein may be modified by site-directed mutagenesis, and that migration within the protein matrix to the active site involves a limited number of pre-existing cavities identified in the interior space of the protein.